Financial Inclusion: Analyzed from Financial Literacy and Use of Financial Technology - Wufron, Wufron; Susilawati, Wati; Nurhasan, Rohimat; Puad, Noor Aimi Binti Mohamad (Journal of Nonformal Education, 2026)
This study aims to determine how financial inclusion in Garut Regency is influenced by fintech usage and financial literacy. The research focuses on the relationship between financial literacy, fintech usage, and the level of financial inclusion among the people of Garut Regency, particularly in the context of regional financial digitalization. The research approach used is quantitative, employing descriptive and verification methods. Data analysis is conducted using multiple regression to examine the influence of fintech and financial literacy on financial inclusion. The population of this study consists of residents of Garut Regency who use fintech services. The research sample is selected using a specific technique appropriate to the study’s objectives. Data is collected through surveys using questionnaires and literature studies to support analysis and discussion. The findings indicate that financial literacy has a positive and significant impact on financial inclusion. Fintech usage also contributes positively and significantly to increasing financial inclusion in society. This study presents a new perspective by discussing the use of fintech in society through dimensions of perception, attitude, intention, and satisfaction related to financial literacy on financial inclusion. Furthermore, this study is conducted in Garut Regency, which has not been extensively researched before, and is related to the implementation of the Regional Financial Access Acceleration Team and Electronification of Regional Government Transactions in promoting financial literacy and inclusion in the region.